Analisis Kolektibilitas Kredit pada Bank Perkreditan Rakyat - Badan Kredit Kecamatan (BPR-BKK) di Kabupaten Banyumas - Puji Lestari; Halomoan Ompusunggu (Universitas Kristen Maranatha, 2007)
This research is aim to know the credit collectibility of BPR-BKK in Banyumas regency of May period 2004-Juni 2005. There are 24 BPR-BKK and 3 BKK operating in 27 subdistrict in Banyumas regency. Data needed is financial statement of BPR-BKK in Banyumas regency that is balance sheet and analyze conducted tabulationly and proportion. Result of calculation indicate that the credit which is the included inperforming loan equal to 93, 76% and credit which is the included in the non performing loan is equal to 6.24%.Keyword s.’ Collectibility, NPL.